Existence of best proximity points in regular cone metric spaces - Kumar L.; Som T. (My University, 2025)
In this paper we have established some conditions which guarantee the existence of the distance between two subsets of a regular cone metric space. Under these conditions we have given a main result which guarantee the existence of best proximity points for cyclic contraction mappings in regular cone metric space, which extends the earlier result of Haghi et al(2011). © 2010 AZJM All rights reserved.